The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1029/2009gl040928
|View full text |Cite
|
Sign up to set email alerts
|

Uplift histories from river profiles

Abstract: [1] Longitudinal river profiles, where elevation of a river bed is plotted as a function of distance along the river bed, contain information about uplift rate. When a region adjacent to a reference level (e.g., sea level) is uplifted, a rapid change in gradient occurs near the river mouth. The erosional process causes this change in gradient to migrate upstream. Thus a river profile is effectively a 'tape recording' of the uplift rate history, provided that the erosional process can be adequately parameterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
219
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 176 publications
(234 citation statements)
references
References 23 publications
5
219
0
1
Order By: Relevance
“…This history is consistent with the conceptual model presented in Fig. 2 and supports the findings of numerous other studies that show that river profiles are sensitive recorders of relative uplift histories (Snyder et al, 2000;Whipple, 2001, 2012;Wobus et al, 2006;Whittaker et al, 2008;Boulton and Whittaker, 2009;Pritchard et al, 2009;Whittaker and Boulton, 2012;Perron and Royden, 2013;Royden and Perron, 2013;Goren et al, 2014;Whittaker and Walker, 2015).…”
Section: Along-strike Patternssupporting
confidence: 79%
See 1 more Smart Citation
“…This history is consistent with the conceptual model presented in Fig. 2 and supports the findings of numerous other studies that show that river profiles are sensitive recorders of relative uplift histories (Snyder et al, 2000;Whipple, 2001, 2012;Wobus et al, 2006;Whittaker et al, 2008;Boulton and Whittaker, 2009;Pritchard et al, 2009;Whittaker and Boulton, 2012;Perron and Royden, 2013;Royden and Perron, 2013;Goren et al, 2014;Whittaker and Walker, 2015).…”
Section: Along-strike Patternssupporting
confidence: 79%
“…Transient landscapes, those landscapes in the process of adjusting to newly imposed boundary conditions, provide the opportunity to interrogate topography for information regarding the timing and magnitude of landscape adjustment to external forcing. As such, studies of transient landscapes have received considerable attention over the past 15 years and serve as a cornerstone of modern tectonic geomorphological studies Whipple, 2001, 2012;Wobus et al, 2006;Pritchard et al, 2009;Perron and Royden, 2013;Royden and Perron, 2013;Gallen et al, 2013;Goren et al, 2014). Most studies that seek to extract tectonic and climate signals from fluvial landscapes rely on river profile analysis; the interpretation of the geometry of river longitudinal profiles, mostly in the context of the detachment-limited river incision model (Howard, 1994;Whipple and Tucker, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…(11) would be a migrating wave of erosion travelling either up or down the catchment (Braun et al, 2015). This wave could also potentially take the form of a shock wave, in which due to the change in gradient the lower reaches of the migrating wave could travel faster than the upper reaches, creating a breaking wave (Smith et al, 2000;Pritchard et al, 2009). The time evolution of Eq.…”
Section: Erosion Within a Single Dimension Systemmentioning
confidence: 99%
“…When river-long profiles are inverted for uplift, erosion is typically assumed to be captured by the stream power model (e.g. Pritchard et al, 2009). Studies of continent-scale inversion have found that the best fit value of k for the stream power model increases by 2 orders of magnitude to fit river profiles in Africa relative to Australia (Rudge et al, 2015).…”
Section: Response Times As a Function Of Model Choicementioning
confidence: 99%
“…Furthermore, many workers have used the framework of the stream power incision model to extract uplift histories (Pritchard et al, 2009;Roberts and White, 2010;Fox et al, 2014;Goren et al, 2014). However, the ability of these studies to extract information from channel profiles is dependent on the concavity index and the slope exponent, n, which are key unknowns within these theoretical models 25 of fluvial incision.…”
mentioning
confidence: 99%